A Conversational Implicature Analysis in James Joyce’s Short Story A Painful Case - Noor, Tehniyat; Salah, Saman; Khan, Saima Yousaf (Annals of Human and Social Sciences, 2025)
The objective of this research is to analyze conversational implicature in James Joyce’s A Painful Case in order to show how implicature is a major part of increasing depth and character development. This paper uses Grice’s Cooperative Principle and maxims of conversation to identify the ways in which Joyce enforces the use of implicatures or indirect meaning, to decipher the mental states of the central character, Mr. James Duffy, and his social relationships with Mrs. Sinico. The deviations are said to consist of flouting, violating, and opting out of maxims with a view of identifying tensions and combat behind seemingly polite intents, emotional meanings which are not communicated overtly and social pressures. These are not just the subtle play with the language by giving a word-play to miscomprehension and meaninglessness of existence. The results enhance the multi-disciplinary study of pragmatics in literary text and suggest ways in which the study of unspoken communication may be applied in modernist texts.